Human papilloma virus DNA: physical mapping and genetic heterogeneity. - Gissmann, L (1976)
The molecular weight of three preparations of human papilloma virus DNA derived from different plantar warts was determined by agarose gel electrophoresis or electron microscopic contour length measurement. It was found to amount to approximately 4.9 X 10(6). Analysis of this DNA after sequential digestion by four different restriction endonucleases (EcoRI, Bam, Hind II, and Hind III) permitted physical mapping of the cleavage sites. Two of the three DNA preparations revealed an identical cleavage pattern, whereas the third one contained two additional cleavage sites.